LOCUS OF CONTROL, KETIDAKPASTIAN LINGKUNGAN DAN SISTEM AKUNTANSI MANAJEMEN - Sutapa .; R Erviana Y (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2010)
The uncertainty of the existing environment will complicate managers in making of theplanning and exercise controlling on of the company's operations. Information was one of thepotential companies that have to received the attention of managers, because in addition to theoperation of information companies can also function as a tool to identification the relevantactivities of the company. Besides environmental uncertainty, information needs of a manageralso influenced by personality factors that of indicated with the locus of control. The problem inthis study is the locus of control the influence relationship of environmental uncertainty on thecharacteristics of management accounting systems information. Population in this researchmanager of manufacturing companies in Surakarta city and the sample of 76 respondents,meanwhile for the data analysis used Structural Equation Models. The use of model equationswith an application program